Heating position effect on internal thermal runaway propagation in large-format lithium iron phosphate battery. (1st November 2022) - Huang, Zonghou; Yu, Yin; Duan, Qiangling; Qin, Peng; Sun, Jinhua; Wang, Qingsong
Highlights: Thermal runaway (TR) characteristics under three heating positions is investigated. TR propagation feature inside the battery under three heating positions is studied. Temperature field of the battery at the critical TR state is analyzed. Thermal runaway propagation mechanism within the battery is revealed. Thermal conductivity-dominated TR propagation influence mechanism is identified. Abstract: Thermal runaway (TR) issues of lithium iron phosphate batteries has become one of the key concerns in the field of new energy vehicles and energy storage. This work systematically investigates the TR propagation (TRP) mechanism inside the LFP battery and the influence of heating position on TR characteristics through experiments. Three different heating modes including heating large, bottom and side surface of the battery with the same heat flux density, are concerned herein. TR characteristic such as temperature, jet velocity, mass, and internal TRP mechanism have been studied. Results show that TR in all three heating modes exhibits jetting white smoke behavior, and TR under large surface heating owns the highest smoke volume, jet velocity and longest duration of jet. Compared with large surface heating, batteries under side and bottom heating exhibits higher overall temperature, peak temperature and temperature increment of large surface and less mass loss. The internal TRP velocity is comparable under side (2.035 ± 0.058 mm/s) and bottom heating (1.942 ± 0.217 mm/s), and the value is approximately 7 times greater than that under large surface heating (0.296 ± 0.007 mm/s). Besides, temperature field of the battery during being heated to TR is described analytically. The voltage drop under large surface heating occurs at the end of internal TRP stage, while voltage drops under side and bottom heating is observed at the initial stage of internal TRP. Finally, the internal TRP mechanism controlled by heat conduction are revealed, and a theoretical model qualitatively describing the TRP velocity within the battery is first proposed, revealing the dominant influencing mechanism of thermal conductivity.